Diel activity patterns of vector mosquito species in the urban environment: Implications for vector control strategies - André B. B. Wilke; Adequate Mhlanga; Allisandra G. Kummer; Chalmers Vasquez; Maday Moreno; William D. Petrie; Art Rodriguez; Christopher Vitek; Gabriel L. Hamer; John-Paul Mutebi; Marco Ajelli (Public Library of Science (PLoS), 2023)
Mathematical models have been widely used to study the population dynamics of mosquitoes as well as to test and validate the effectiveness of arbovirus outbreak responses and mosquito control strategies. The objective of this study is to assess the diel activity of mosquitoes in Miami-Dade, Florida, and Brownsville, Texas, the most affected areas during the Zika outbreak in 2016-2017, and to evaluate the effectiveness of simulated adulticide treatments on local mosquito populations. To assess variations in the diel activity patterns, mosquitoes were collected hourly for 96 hours once a month from May through November 2019 in Miami-Dade County, Florida, and Brownsville, Texas. We then performed a PERMANOVA followed by a SIMPER analysis to assess whether the abundance and species richness significantly varies at different hours of the day. Finally, we used a mathematical model to simulate the population dynamics of 5 mosquito vector species and evaluate the effectiveness of the simulated adulticide applications. A total of 14,502 mosquitoes comprising 17 species were collected in Brownsville and 10,948 mosquitoes comprising 19 species were collected in Miami-Dade County. Aedes aegypti was the most common mosquito species collected every hour in both cities and peaking in abundance in the morning and the evening. Our modeling results indicate that the effectiveness of adulticide applications varied greatly depending on the hour of the treatment. In both study locations, 9 PM was the best time for adulticide applications targeting all mosquito vector species; mornings/afternoons (9 AM- 5 PM) yielded low effectiveness, especially for Culex species, while at night (12 AM- 6 AM) the effectiveness was particularly low for Aedes species. Our results indicate that the timing of adulticide spraying interventions should be carefully considered by local authorities based on the ecology of the target mosquito species in the focus area. Author summary Mathematical models have been widely used to study vector mosquitoes as well as to test the effectiveness of arbovirus outbreak response and mosquito control strategies. However, due to the lack of empirical data, there are no studies focusing on the effectiveness of adulticide applications at different hours of the day to control different mosquito populations. This study leveraged a unique dataset in which approximately 25,000 mosquitoes comprising 19 species were collected hourly in Miami-Dade County, Florida, and Brownsville, Texas. We then developed a mathematical model to simulate the population dynamics of five mosquito vector species to evaluate the effectiveness of adulticide spraying at different times of the day and at different frequencies. Mosquito community composition and abundance varied significantly throughout the day in both Brownsville and Miami-Dade County with more than 10-fold differences during the day. Depending on the target vector species, the application of adulticides at a given hour of the day may lead to drastically different results, although we found some common patterns such as the remarkable effectiveness of interventions performed at 9 PM.